Mapping and interpretation of bed-reflection power from a surge-type polythermal glacier, Yukon, Canada - Wilson, Nat J.; Flowers, Gwenn E.; Mingo, Laurent (Annals of glaciology, 2014)
Bed-reflection power (BRP) from ice-penetrating radar has been used to make inferences about subglacial conditions and processes, yet is subject to confounding influences, including englacial attenuation and bed geometry. We use radar data collected in 2008–11 from a polythermal glacier to compute BRP with the aim of relating BRP to basal conditions. We examine the relationship between raw BRP and ice thickness, apparent bed slope and thickness of the englacial scattering layer as a proxy for internal reflection power. We then analyze a corrected form of the BRP with a graph-segmentation algorithm to delineate areas of high and low reflection power. Low corrected BRP values are found near the glacier terminus where the bed is most likely to be cold, while high corrected BRP is found in the region thought to be undergoing a slow surge. We find a spatial correlation between high BRP and high values of subglacial hydraulic upstream area, suggestive of a hydrological control on BRP. Whereas in dominantly cold glaciers BRP seems to distinguish cold from temperate regions of the bed, BRP in a polythermal glacier with a substantial volume of temperate ice may be a more complex product of thermal and hydrological conditions.